"Teacher characteristics they value": London upper secondary students' perspectives. Issue 1 (2nd January 2022) - Minott, Mark
ABSTRACT: The purpose of this qualitative study is to provide answers to the research question, "What teacher characteristics do London upper Secondary school students value?" Using convenient or opportunity sampling, 51 Grade 12 and 13 students ages 16–18 in a south-west London secondary school were interviewed using a face-to-face method. The analysis of the data revealed that students in this study valued teacher affective and pedagogic characteristics. These include teachers being caring, "relatable" and empathic. Possessing personal traits (agreeableness – characterised by soft-voice, gentle disposition, patience, high expectation of self and students and helpfulness), pedagogic practices (articulateness, teaching that connects with their out-of-school life and takes their perspective in mind; passion; discipline; professionalism and teaching material free of errors) and the infusion of humour during lessons. Firstly, the study reinforced the idea that London, upper secondary students do hold views about teacher characteristics they value and should be given the opportunity to express their opinions. Secondly, Teachers use of humour as appropriate is recommended even though there seems to be no consensus in the literature in this regard. Finally, beginning teachers or newly qualified teachers (NQTs) as well as seasoned teachers should nurture and utilise their affective characteristics. This is so because, as shown in this study, not doing so can result in students being negatively impacted long-term.